Copper-catalyzed oxidative C–H/C–H cross-coupling of benzamides and thiophenes1. Issue 64 (18th August 2015) - Zhao, Sheng; Yuan, Jun; Li, Yi-Chen; Shi, Bing-Feng
<x xml:space="preserve">Abstract</x> A copper-catalyzed oxidative C–H/C–H cross-coupling of benzamides and thiophenes is described.